Financial Analysis of Monarch Airlines - Joglekar, Ameya (2014)
This report is an individual extension to the group report submitted to Monarch Airlines Ltd in part submission for the management project. The report covers a detailed financial statement analysis of Monarch Airlines Ltd. and one of its competitor Jet2.com as a peer comparison. As the budget airline industry is a very saturated and highly competitive industry, this study should prove to be useful for Monarch Airlines in their future decision making by reflecting on past performance and highlighting key factors contributing to either positive or negative results.